PENGARUH PENGUATAN SPIRITUAL KEAGAMAAN TERHADAP KEHIDUPAN MAHASISWA DI POLITEKNIK NEGERI JAKARTA - Irwan Prasetya; Al Haura Dzatil Himmah; Nurul Aini, (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2025)
The development of technology and the strong impact of globalization make it difficult for students to maintain a balance between academic and social life. In this situation, students face a variety of major challenges, such as the rise of promiscuity and the high rate of college dropouts. Religious spiritual strengthening can be one of the solutions to face these serious challenges. This research uses descriptive qualitative methods that include observation, interviews, and document analysis as data collection techniques. The subjects of this study consisted of 15 students who were active in academic and social activities, and came from 7 different majors. The results showed that strengthening religious spirituality can increase learning motivation, stabilize emotions, and create peace of mind. Students with high religious spirituality tend to have a balanced life and a good academic performance index (GPA). It can be concluded that religious spiritual reinforcement is very important for students' academic and social development.